A real-world study of antifibrotic drugs-related adverse events based on the United States food and drug administration adverse event reporting system and VigiAccess databases - He, Menglin; Yang, Taoran; Zhou, Jian; Wang, Rurong; Li, Xuehan (Frontiers in Pharmacology, 2024)
Objectives: This study aims to investigate adverse events (AEs) and adverse drug reactions (ADRs) associated with pirfenidone and nintedanib, two antifibrotic drugs used to treat idiopathic pulmonary fibrosis (IPF). Methods: Reporting odds ratio (ROR) and proportional reporting ratio (PRR) analyses were conducted to assess the association between these drugs and signals at both the preferred term (PT) and system organ class (SOC) levels. Results: 55,949 reports for pirfenidone and 35,884 reports for nintedanib were obtained from the FAERS database. The VigiAccess database provided 37,187 reports for pirfenidone and 23,134 reports for nintedanib. Male patients and individuals over the age of 65 were more likely to report AEs. Gastrointestinal disorders emerged as the most significant signal at SOC level for both drugs. Furthermore, nausea, diarrhoea, and decreased appetite were observed at the PT level. We further identified notable signals, including hemiplegic migraine for pirfenidone and asthenia, constipation, and flatulence for nintedanib, which were previously unknown or underestimated ADRs. Conclusion: This study has identified AEs and ADRs associated with pirfenidone and nintedanib, confirming that the majority of the corresponding label information indicates relative safety. However, it is essential to take unexpected risk signals seriously, necessitating further research to manage the safety profiles of these drugs.